ACTUALIZATION OF THE TASKS OF ACCOUNTING AND ANALYSIS IN THE CONDITIONS OF DIGITAL SHIFTS OF THE ECONOMY (Economic journal of Lesya Ukrainka Volyn National University, 2021)
During the transition of the economy to an innovative path of development, requirements for information and analytical support for the entire management system are growing. In the conditions of the computer form of accounting, the necessary information is contained in the database, access to which accounting and management employees have access in the mode of dialogue. Qualitative development of digital services in accounting aims not only to minimize the human factor in decision-making, but also to obtain fast quality information about processes. Transformation of accounting and analysis in the context of digitalization of the economy faces a number of problems. Accounting, maintaining its relevance and query of the product created, should become a clear component of the system of obtaining, processing, and transferring economic information. Before accounting, the task is to reorient from the control function to an informative one based on the systematization of issues of digital transformation of the organization. The target focus of business analysis is the analytical provision of effective corporate governance, which involves close interaction between shareholders and management of the company, as well as with other stakeholders (stakeholders). Business analysis can serve as one of the effective tools that can solve a number of problems and contradictions of domestic corporate governance.The modern concept of analysis should include the study of business opportunities in creating value for stakeholders, in the development of the entire ecosystem of business, that is, the aggregate wealth of all persons involved in the company, and not only maximizing the well-being of shareholders.
Keywords: accounting, business analytics, digital economy, information, management